2017
DOI: 10.1111/jpc.13746
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in 22q11.2 deletion syndrome: The child's perspective

Abstract: This study is the first to explore HRQOL from the perspective of the child with 22qDS, and our findings support the existing literature that this condition is associated with a poor HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…To contextualize the impact of congenital athymia on HRQoL, scores also were compared with similarly debilitating congenital conditions with substantial burden for patients and families. The total score of patients with congenital athymia was similar to that of patients with spinal muscular atrophy (53.35) and 22q11.2 deletion syndrome (50.98) on the PedsQL parent proxy report [32,33]. To the authors' knowledge, this is the first study evaluating quality of life in patients with congenital athymia.…”
Section: Discussionsupporting
confidence: 52%
“…To contextualize the impact of congenital athymia on HRQoL, scores also were compared with similarly debilitating congenital conditions with substantial burden for patients and families. The total score of patients with congenital athymia was similar to that of patients with spinal muscular atrophy (53.35) and 22q11.2 deletion syndrome (50.98) on the PedsQL parent proxy report [32,33]. To the authors' knowledge, this is the first study evaluating quality of life in patients with congenital athymia.…”
Section: Discussionsupporting
confidence: 52%
“…This was lower in sick infants than in healthy infants and affected males more than females. Other researchers who also showed that quality of life in children and adolescents with DS 22q11.2 is lower than in healthy people and in people with other types of chronic diseases were Joyce et al [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…The degree of dependence in order to perform daily activities such as talking, due to malformations in the palate, and walking or doing sports normally, due to cardiac manifestations, highlight this aspect. Difficulties in adaptation to the environment and school or work integration are other issues that often have a negative impact on the life of these patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The largest number of ICF categories in Activities and Participation and Environmental factors in the final ICF list reflects the high contribution of the condition in the life of 22q11.2DS children and may also be related to the need of the experts in assessing influences in 22q11.2DS children's functioning in the new biopsychosocial model, where the experts see beyond the physical impact of the syndrome and seek to understand the real influence in patient's functioning. Few studies have been focusing on establish and measuring health related to quality of life as a clinical outcome in children with 22qDS; a recent study showed that children with 22qDS had a significantly poorer quality of life when compared to age-matched cohorts of healthy children and children with chronic disease (33) .…”
Section: Discussionmentioning
confidence: 99%